1983
DOI: 10.1016/s0022-5347(17)52282-x
|View full text |Cite
|
Sign up to set email alerts
|

Penicillinase-Producing Neisseria Gonorrhoeae in Great Britain, 1977-81: Alarming Increase in Incidence and Recent Development of Endemic Transmission

Abstract: 23 Cogswell JJ. Forced oscillation technique for determination of resistance to breathing in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…3 The original foci of gonococcal infection with PPNG strains were in the Far East and West Africa, but since 1976 infection with PPNG strains has established itself as endemic in most parts of the world, and the increase in incidence has been exponential. 4 The incidence of PPNG strains in some areas of South East Asia is now reported to be as high as 500o,5 and a similar level has been reported in Nigeria (Osoba A 0, unpublished data). In the United Kingdom the overall incidence of PPNG in 1982 was estimated at 2%, but some sexually transmitted disease (STD) clinics in central London reported an incidence of more than 707o, and abandoned the use of penicillin for the treatment of gonorrhoea in heterosexual patients.6 There is clearly an urgent need to evaluate treatment regimens that are alternatives to penicillin, and that are effective in a single dose, non-toxic and cheap.…”
Section: Introductionmentioning
confidence: 60%
“…3 The original foci of gonococcal infection with PPNG strains were in the Far East and West Africa, but since 1976 infection with PPNG strains has established itself as endemic in most parts of the world, and the increase in incidence has been exponential. 4 The incidence of PPNG strains in some areas of South East Asia is now reported to be as high as 500o,5 and a similar level has been reported in Nigeria (Osoba A 0, unpublished data). In the United Kingdom the overall incidence of PPNG in 1982 was estimated at 2%, but some sexually transmitted disease (STD) clinics in central London reported an incidence of more than 707o, and abandoned the use of penicillin for the treatment of gonorrhoea in heterosexual patients.6 There is clearly an urgent need to evaluate treatment regimens that are alternatives to penicillin, and that are effective in a single dose, non-toxic and cheap.…”
Section: Introductionmentioning
confidence: 60%
“…For example, AR pathogens endemic in many developing countries have been recovered from recent returnees in the United States and Europe who were presumed to be infected during their visits abroad (table 1) [3,36,56]. When strains causing infections show unusual antibiotic resistance patterns, they may have been imported from countries where such resistance is commonplace [57].…”
Section: Surveillance Of Importation Of Ar Bacteriamentioning
confidence: 99%
“…Before then, PPNG was virtually unknown in Britain, and treatment of gonorrhea was usually carried out empirically with penicillin. In the subsequent decade, PPNG became endemic in Britain, and penicillin could no longer be used empirically [3]. More recently, Smith et al [4] have shown that the majority of cases of infection due to quinolone-resistant Campylobacter in Minnesota in 1996-1997 were associated with international travel.…”
mentioning
confidence: 99%
“…Thereafter infections caused b y PPNG strains rose, the n u m b e r of reported cases doub,ling annual'ly from 1977 to 1982 giving rise to fears of an .epidemic (8). Thereafter infections caused b y PPNG strains rose, the n u m b e r of reported cases doub,ling annual'ly from 1977 to 1982 giving rise to fears of an .epidemic (8).…”
Section: Introductionmentioning
confidence: 99%